Systems, habitats or places: evaluating the potential role of landscape character assessment in operationalising the ecosystem approach. (3rd October 2018) - Morrison, Rachel; Barker, Adam; Handley, John
Abstract: A key challenge for research and practice is to understand how the ecosystem approach can be rolled out in spatial planning, management and decision-making. Any framework used to apply the ecosystem approach needs to not only be environmentally coherent but also socially meaningful. Drawing on semi-structured interviews and case studies, this paper examines the potential role of one place-based approach, landscape character assessment, as a medium to ensure socio-ecological relevance in operationalising the ecosystem approach. Our findings show that although place-based approaches have value as frameworks for distilling the ecosystem approach into a manageable form, their ecological relevance is a subject of debate. However, the potential relationship between landscape character, function and ecosystem services presented a powerful pathway for operationalising the ecosystem approach. The ecosystem approach may, in turn, complement landscape character assessment by providing a framework for exploring the functional dimension of landscape condition.